CORPUS STUDY IN LEXICOGRAPHIC RESEARCH (International journal of artificial intelligence, 2024)
Technologies, especially the results obtained in artificial intelligence and machine learning or deep learning prove that the language model and its knowledge based data can be created through a corpus. This article contains analytical materials related to scientific theories conducted in this field. The theoretical ideas included in this analysis will serve as a source for practical work to be carried out for the Uzbek language in the future.